The Expression of a Small Fraction of Cellular Genes Is Changed in Response to Histone Hyperacetylation - Van Lint, Carine (Gene Expr, 2018)
Posttranslational modifications of histones in chromatin are emerging as an important mechanism in the regulation of gene expression. Changes in histone acetylation levels occur during many nuclear processes such as replication, transcriptional silencing, and activation. Histone acetylation levels represent the result of a dynamic equilibrium between competing histone deacetylase(s) and histone acetylase(s). We have used two new specific inhibitors of histone deacetylase, trichostatin A (TSA) and trapoxin (TPX), to probe the effect of histone hyperacetylation on gene expression. We confirm that both drugs block histone deacetylase activity and have no detectable effects on histone acetylation rates in human lymphoid cell lines. Treatment with either TSA or TPX results in the transcriptional activation of HIV-1 gene expression in latently infected cell lines. In contrast, TSA and TPX cause a rapid decrease in c-myc gene expression and no change in the expression of the gene for glycer aldehyde-3-phosphate dehydrogenase (GAPDH). Using differential display to compare the differences in gene expression between untreated cells and cells treated with TSA, we found that the expression of ∼2% of cellular genes (8 genes out of ∼340 examined) changes in response to TSA treatment. These results demonstrate that the transcriptional regulation of a restricted set of cellular genes is uniquely sensitive to the degree of histone acetylation in chromatin.